1999
DOI: 10.1530/eje.0.1400577
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I production by adult rat hepatocytes is stimulated by transforming growth factor-alpha and transforming growth factor-beta1

Abstract: Previously, we have observed that epidermal growth factor (EGF), a potent mitogen for cultured hepatocytes, stimulates the production of IGF-I and IGF-binding proteins (IGFBPs) by cultured hepatocytes from adult rats. This study was undertaken to investigate the possibility that other growth factors of hepatic origin could specifically be involved in the regulation of IGF-I and IGFBP expression. The effects of transforming growth factor-a (TGF-a), through EGF receptors to induce a mitogenic response, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Low concentrations stimulated ErbB2 expression at 72 h, but the highest doses inhibited it. The stimulatory effect of TGF-␤ 1 on ErbB2 levels at low concentrations may relate to its ability to induce IGF-1 expression (34), which we have shown also induces ErbB2 (data not shown). Cells treated with the highest doses of TGF-␤ 1 were apoptotic and likely unable to synthesize a normally induced protein, such as ErbB2.…”
Section: Hepatocytes Show Increased Protein Tyrosine Phosphorylation mentioning
confidence: 72%
“…Low concentrations stimulated ErbB2 expression at 72 h, but the highest doses inhibited it. The stimulatory effect of TGF-␤ 1 on ErbB2 levels at low concentrations may relate to its ability to induce IGF-1 expression (34), which we have shown also induces ErbB2 (data not shown). Cells treated with the highest doses of TGF-␤ 1 were apoptotic and likely unable to synthesize a normally induced protein, such as ErbB2.…”
Section: Hepatocytes Show Increased Protein Tyrosine Phosphorylation mentioning
confidence: 72%
“…This would argue for involvement of the type II IGF-R, also known as the cation-independent mannose 6 phosphate receptor, involved in intracellular trafficking (68) as opposed to the type I IGF-R, which can be activated by insulin at the concentrations used in our assays (69). Previous studies have reported that TGF-␤ can induce IGF synthesis (70,71), which we believe explains the lack of an absolute requirement for IGF in TGF-␤-activated cells compared with CTGF-treated cells. In this manner, TGF-␤ induces the expression of multiple growth factors that are required for the completion of the developmental program.…”
Section: Discussionmentioning
confidence: 92%
“…EGF stimulates the production of IGF-I and IGFBP in cultured hepatocytes from adult rats [53]. TGF-a and TGF-b stimulate IGF-I and IGFBP secretion by cultured rat hepatocytes although no change in the abundance of IGF-I and IGFBP mRNA was observed [54]. Furthermore, type I IGF receptors, which are considered responsible for IGF-I-induced mitogenic action, are not present in cultured adult rat hepatocytes [13].…”
Section: Discussionmentioning
confidence: 99%